Pengaruh Pengungkapan ESG terhadap Kinerja Keuangan Perusahaan Pertambangan di Indonesia - Surianto, Nurul Maghfirah; Jauhari, Yustika; Muflikhah, Itsna; Azisah, Andi Nurul; Wahdana, Nadhiyah Putri (Tangible Journal, 2025)
This study aims to analyze the effect of environmental, social, and governance (ESG) disclosure on the financial performance of companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024. The data used is secondary data derived from sustainability reports, annual reports, and ESG assessments published by independent rating agencies. The sample was selected using a targeted selection method based on specific criteria, such as the availability of ESG scores and financial reports for the observation period. The independent variable in this study is the level of ESG disclosure, while the dependent variable is financial performance measured using return on assets (ROA) as the sole indicator of profitability. Data analysis was performed using multiple linear regression to test the relationship between ESG disclosure and financial performance. The results of the study indicate that ESG disclosure has a positive and significant effect on a company's ROA. These results suggest that increased ESG disclosure can strengthen investor confidence and improve risk management effectiveness, which will ultimately lead to better financial performance. This study provides recommendations for companies in Indonesia to improve transparency and implement sustainable practices in order to achieve long-term economic growth.